RAICEX: A Successful Story of the Spanish Scientific Diaspora - Ortega-Paino, Eva; Oliver, Eduardo (Frontiers in Research Metrics and Analytics, 2022)
RAICEX (Red de Asociaciones de Investigadores y Científicos Españoles en el Exterior), the Network of Associations of Spanish Researchers and Scientist Abroad, consists of more than 4,000 Spanish researchers distributed in 18 countries in 5 different continents. RAICEX was established in July 2018 by 15 foundational members: the associations of Spanish Researchers in the USA, México, Ireland, Sweden, Denmark, France, Italy, Japan, Australia, China, UK, Germany, Switzerland, Belgium and Norway. Since then, 3 more associations have joined: Emirates, Netherlands and South Africa. RAICEX was born with the main goal: “promoting the exchange of experiences and knowledge between Spanish researchers and scientists abroad and all the stakeholders of the Spanish System of Science, Technology and Innovation (SECTI), serving as an advisory body, information channel and catalyst for international relations in scientific matters, contributing to the progress of science”. Their main objectives are: 1) to provide support to researchers and scientists in mobility and personal development, offering training, information and guidance, as well as providing contact with all the other associations that make up the global network; 2) to disseminate and give visibility to the value of Science and the work of researchers and scientists, promoting communication of the advances of knowledge in all areas of society; 3) to promote international relations and cooperation between researchers / scientists and public and private organisations, from a global perspective; 4) to share the acquired knowledge and experience in different research and science systems abroad to advise, provide feedback and contribute to the progress of the whole SECTI. In this Case Study a particular scenario of the Spanish scientific diaspora, including history, reasons for going abroad, and consequences for the Spanish R&D system, shall be introduced to readers. The impact that RAICEX and its foundational members have had in the Spanish National System since the creation of the first community in the UK by 2012 will also be discussed. RAICEX’s activities range from providing advice to newcomers and carrying out science dissemination, to becoming an advisory body to governments and institutions. The Spanish scientific diaspora is an extensive network committed to cooperation and brain connection.